Retraction Notice: Tocotrienols and its Role in Cardiovascular Health- a Lead for Drug Design - Vasanthi, Hannah R.; Parameswari, R. P.; Das, Dipak K. (Current Pharmaceutical Design, 2021)
The article has been retracted by the Editorial office of the journal Current Pharmaceutical Design, due to some inconsistencies in the article [1]. The article appeared to be copied verbatim from published papers. Upon checking these facts, we have established that considerable portions of this review are made up of text copied verbatim from other published material. The Publisher has retracted this article in accordance with good ethical practices. REFERENCE [1] Vasanthi HR, Parameswari RP and Das DK. Tocotrienols and its Role in Cardiovascular Health- a Lead for Drug Design. Curr Pharm Des 2011; 17(21): 2170-5. Bentham Science apologizes to the readers of the journal for any inconvenience this may have caused. The Bentham Editorial Policy on Article Retraction can be found at https://benthamscience.com/editorial-policies-main.php. Bentham Science Disclaimer: It is a condition of publication that manuscripts submitted to this journal have not been published and will not be simultaneously submitted or published elsewhere. Furthermore, any data, illustration, structure or table that has been published elsewhere must be reported, and copyright permission for reproduction must be obtained. Plagiarism is strictly forbidden, and by submitting the article for publication the authors agree that the publishers have the legal right to take appropriate action against the authors, if plagiarism or fabricated information is discovered. By submitting a manuscript, the authors agree that the copyright of their article is transferred to the publishers if and when the article is accepted for publication.